2021
DOI: 10.1177/08445621211058328
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Scope of Practice Enactment Among Primary Care Registered Nurses

Abstract: Background Scope of practice enactment is poorly understood in the primary care setting. Purpose The following research objectives were addressed: (1) to revise and adapt the Actual Scope of Practice (ASCOP) questionnaire for use in the primary care setting, and (2) to determine internal consistency, construct validity, and sensitivity of the modified instrument. Methods To address the first objective, a narrative literature review and synthesis and an expert panel review was conducted. To address the second o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…For example, a Canadian study conducted by Déry et al [3] had an overall mean score for ASCOP of 3.21 out of 6, indicating that, on average, nurses occasionally performed nursing skills measured by the ASCOP scale. In another study carried out in Canada, a higher overall item mean score of 4.8 (out of 6.0) was reported [17]. Furthermore, D'Amour et al [14] conducted a study where the overall mean score for the ASCOP was 3.47 out of 6.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, a Canadian study conducted by Déry et al [3] had an overall mean score for ASCOP of 3.21 out of 6, indicating that, on average, nurses occasionally performed nursing skills measured by the ASCOP scale. In another study carried out in Canada, a higher overall item mean score of 4.8 (out of 6.0) was reported [17]. Furthermore, D'Amour et al [14] conducted a study where the overall mean score for the ASCOP was 3.47 out of 6.…”
Section: Discussionmentioning
confidence: 94%
“…Braithwaite [17] studied 178 nurses in primary healthcare institutions in Canada, using the ASCOP questionnaire with some adjustments to be appropriate for measuring the scope of nursing practice in primary healthcare institutions. The results revealed that the average score of subjects was 5.16 out of 6, indicating that nurses almost always carry out activities related to the enactment of nursing scope of practice [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,13,24 Nurses' scope of practice is defined as the standards of care that are set by regulatory bodies, reflecting the knowledge and skills expected of nurses. 31,32 In the context of a global nursing shortage, nurses' practice should be optimized to ensure efficiency and continuity of care. 33,34 However, many work characteristics have a significant impact on nurses' scope of practice.…”
Section: Work Environment and Nursing Practice During The Pandemicmentioning
confidence: 99%
“…Nursing homes, which can be private, or run by the Health Maintenance Organization, or government, offer services to older adults who need assistance with their daily function. This type of facility often has wings based on the level of function: moderate to severe decrease in daily function; severe disability with permanent mobility limitation; and mentally frail with functional limitation other than cognitive deterioration that requires supervision and aid in daily care (Braithwaite et al, 2021; Schmitz & Stroka‐Wetsch, 2020).…”
Section: Introductionmentioning
confidence: 99%